(untitled) (Anclajes, 2023)
The novels by Juan Pablo Villalobos have managed to position itself, through his six novels, in a small but significant niche in contemporary Mexican literature: non-solemn literature. Said character of his artistic proposal involves his narrative from different ethical-aesthetic trenches, such as the recurring stylizations of humor, the predilection for non-serious themes such as corporality, nomadism, criticism of power, drug trafficking, among other topics. The opposition to the established order finds in Villalobos different channels from which to enunciate. The novelistic work takes advantage of formal tools as one more weapon against the conventions that could be considered conservative in literature. An example of this may be the function that generic hybridization fulfills. The different ethical-aesthetic implications of generic hybridization in Si viviéramos en un lugar normal are the subject of the article.